2022
DOI: 10.1021/acssuschemeng.2c00237
|View full text |Cite
|
Sign up to set email alerts
|

Catalyst Recycling in the Reactive Distillation of Primary Alcohols to Olefins Using a Phosphoric Acid Catalyst

Abstract: Olefins are essential basic chemicals in all areas of the chemical industry and can be produced from alcohols by dehydration. The amount of alcohols produced from biomass sources is expected to rise in the next decade. Various heterogeneously catalyzed processes have been developed in previous works operating at a high reaction temperature of 350 °C to obtain olefins from alcohols. In this work, we present the conversion of C7 to C12 α-alcohols to the corresponding olefins using phosphoric acid as a strong ino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…This may be due to an increased formation of side products, in particular n -butyl ester, at a higher temperature in the presence of p -TsOH·H 2 O. 49 The pressure also showed a significant influence as a hydrogen pressure of 20 bar increased the yield, whereas it reduced the yield for 2-BuOH (Table 2, entry 9–11). The highest yield of 64% (VA : 2-MBA = 2 : 1) was obtained with 1 mL acetic acid, 20 bar H 2 , without p -TsOH·H 2 O at 160 °C (Table 2, entry 10).…”
Section: Resultsmentioning
confidence: 99%
“…This may be due to an increased formation of side products, in particular n -butyl ester, at a higher temperature in the presence of p -TsOH·H 2 O. 49 The pressure also showed a significant influence as a hydrogen pressure of 20 bar increased the yield, whereas it reduced the yield for 2-BuOH (Table 2, entry 9–11). The highest yield of 64% (VA : 2-MBA = 2 : 1) was obtained with 1 mL acetic acid, 20 bar H 2 , without p -TsOH·H 2 O at 160 °C (Table 2, entry 10).…”
Section: Resultsmentioning
confidence: 99%
“…On the first glance this result appears to be in contrast to the dehydration study done by Vorholt et al who obtained a formation of alkenes from primary alcohols with phosphoric acid as a catalyst. 19 However, higher reaction temperatures (190-200 °C) as well as much higher catalyst loadings (1 eq.) were used in their work.…”
Section: Dehydration By Brønsted Acidsmentioning
confidence: 99%
“…A further very recent study by Vorholt et al demonstrated that reaction temperatures below 200 °C, can be achieved also with Brønsted acids. 19 In detail, the Vorholt group used phosphoric acid in stoichiometric amount and succeeded in dehydrating 1-octanol at 190 °C mainly to the ether but also in lower amounts to the alkenes.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, phosphoric acids have long been utilized as homogeneous Brønsted acid catalysts for the conversion of alcohols and ethers benefiting from their ability to activate the CÀ O bonds (Figure 1b, (i)). [12] Subsequently, metal oxide supported phosphoric acids have been developed and applied to the hydrogenolysis of CÀ O bonds by supporting transition metal nanoparticles on them (Figure 1b, (ii)). [13] In our approach, instead of directly using phosphoric acid itself, Al(PO 3 ) 3 is employed as the catalyst support, and by supporting Pt nanoparticles on Al(PO 3 ) 3 (Pt/Al(PO 3 ) 3 ), phosphoric acid-like Brønsted acid sites are formed indirectly via the Pt-catalyzed cleavage of H 2 (Figure 1b, (iii)).…”
Section: Introductionmentioning
confidence: 99%